Haptoglobin genotype and cerebrovascular disease incidence in type 1 diabetes - Costacou, Tina (2014)
OBJECTIVE: We prospectively evaluated the Haptoglobin (Hp)-stroke association in type 1 diabetes and hypothesized that despite increasing the risk for coronary artery disease, the presence of the Hp 2 allele would lower stroke incidence. METHODS: Participants from the Epidemiology of Diabetes Complications study without prevalent stroke and Hp available were evaluated (n=607; mean age, 27.6 and duration, 19.3 years). RESULTS: During 22 years of follow-up, stroke incidence did not differ by Hp genotype (p=0.49). Restricting analyses to those diagnosed with diabetes ≥1965 (13% mortality versus 40% in the <1965 cohort) to diminish potential survival bias, the adjusted HR for Hp 1-1 was 3.08 (95% CI=0.81-11.77, p=0.10). Further stratifying by hypertension prevalence, an increased stroke incidence was observed with Hp 1-1 only in those with hypertension (HR=7.03, 95% CI=1.42-34.89, p=0.02). CONCLUSIONS: Despite the protective effect against vascular diabetes complications, a borderline increased risk for stroke was observed with Hp 1-1 in type 1 diabetes. This mixed Hp effect on cardiovascular risk by outcome studied merits further investigation and cautions against the universal application of preventive therapies across all Hp genotypes.